Insulin Exhibits an Antiproliferative and Hypertrophic Effect in First Trimester Human Extravillous Trophoblasts. (April 2017) - Silva, Cláudia; Nunes, Catarina; Correia-Branco, Ana; Araújo, João R.; Martel, Fátima
Our aim was to investigate the effect of high levels of glucose, insulin, leptin, and tumor necrosis factor alpha, biomarkers of diabetes in pregnancy, in the process of placentation, using as a cell model a first trimester extravillous human trophoblast cell line (HTR8/SVneo cells). Exposure of HTR8/SVneo cells for 24 hours to either glucose (20 mmol/L) or leptin (25-100 ng/mL) did not cause significant changes in cell proliferation and viability. Tumor necrosis factor alpha (24 hours; 10-100 ng/L) caused a small decrease (10%) in cell proliferation and an increase (9%) in cell viability; however, both effects disappeared when exposure time was increased. Insulin (24 hours; 1-10 nmol/L) caused a concentration- and time-dependent decrease (10%-20%) in cell proliferation; the effect of insulin (10 nmol/L) was more pronounced after a 48 hours exposure (35%). In contrast, exposure to insulin (10 nmol/L; 48 hours) showed no significant effect on cell viability, apoptosis, and migration capacity. Insulin appears to cause hypertrophy of HTR8/SVneo cells as it reduces the cell mitotic index while increasing the culture protein content. The antiproliferative effect of insulin seems to involve activation of mammalian target of rapamycin, phosphoinositide 3-kinase, and p38 mitogen-activated protein kinase. Finally, simvastatin and the polyphenol quercetin potentiated the antiproliferative effect of insulin; on the contrary, the polyphenol resveratrol, the polyunsaturated fatty acids eicosapentaenoic and docosahexaenoic acids, and folic acid were not able to change it. In conclusion, we show that insulin has an antiproliferative and hypertrophic effect on a first trimester extravillous human trophoblast cell line. So insulin might affect the process of placentation.